Auto-negotiation time division MAC protocol for periodical data gathering in sensor networks - ZENG Yi; HU Bo; LIU Shun-jia (Tongxin xuebao)
On the analysis of data flow characteristics in periodical data gathering applications in wireless sensor net- works, an auto-negotiation time division MAC protocol based on auto-negotiation slot allocation scheme was proposed. The slot allocation is carried out in the adaptive, distributed and localized manner. The simulation shows that power con- sumption in our protocol has been decreased to the one thirty of that in TAG protocol with extended ACK re-transmission scheme, while delivery ratio and maximum data latency suffer no deterioration.